2005
DOI: 10.1103/physrevb.72.224206
|View full text |Cite
|
Sign up to set email alerts
|

Continuum limit of amorphous elastic bodies. III. Three-dimensional systems

Abstract: Extending recent numerical studies on two dimensional amorphous bodies, we characterize the approach of elastic continuum limit in three dimensional (weakly polydisperse) Lennard-Jones systems. While performing a systematic finite-size analysis (for two different quench protocols) we investigate the non-affine displacement field under external strain, the linear response to an external delta force and the low-frequency harmonic eigenmodes and their density distribution. Qualitatively similar behavior is found … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
238
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(284 citation statements)
references
References 30 publications
41
238
0
2
Order By: Relevance
“…For example, in 3D Lennard-Jones simulations of elastic deformation of a polydisperse glass, Leonforte and coworkers observed non-uniform non-affine atomic displacements and measured a correlation length of ∼ 23σ [37]. More recently, Dmowski and coworkers suggested, from x-ray scattering data, that only about three-quarters of the atoms in a metallic glass deform elastically, with the remainder being anelastic "liquidlike" material.…”
Section: Characteristics Of Non-affine Displacementsmentioning
confidence: 99%
“…For example, in 3D Lennard-Jones simulations of elastic deformation of a polydisperse glass, Leonforte and coworkers observed non-uniform non-affine atomic displacements and measured a correlation length of ∼ 23σ [37]. More recently, Dmowski and coworkers suggested, from x-ray scattering data, that only about three-quarters of the atoms in a metallic glass deform elastically, with the remainder being anelastic "liquidlike" material.…”
Section: Characteristics Of Non-affine Displacementsmentioning
confidence: 99%
“…The third C K is the contribution from the kinetic energy to the modulus, which is much smaller than the other two terms and can be neglected for dense systems. For amorphous materials, the non-affine term C N is an important contribution, comparable in magnitude with the affine term C B [4,5,7]. The three approaches to measure the local modulus described above evaluate this non-affine component C N in different ways.…”
Section: Introductionmentioning
confidence: 99%
“…The local heterogeneity in the elastic properties is reflected by the existence of a strong non-affine character in the elastic deformation of the material [4][5][6][7]: the displacement field at small scale is not obtained from the macroscopic strain, but the atoms undergo an extra relaxation described as a non-affine displacement, which has long range spatial correlations due to the elastic character of the problem [8,9]. The scale ξ of the elastic heterogeneities can be assessed by measuring the local elastic properties as a function of a coarse graining size, and monitoring the convergence towards macroscopic properties [3].…”
Section: Introductionmentioning
confidence: 99%
“…For Lennard-Jones glasses, Tanguy and co-workers [6][7][8][9] showed that the disorder can give rise to important corrections to naive estimates for the elastic moduli. O'Hern et.…”
mentioning
confidence: 99%